Alterations in endocytic protein expression with increasing age in the transgenic APP695 V717I London mouse model of amyloid pathology: implications for Alzheimer's disease. Issue 15 (18th October 2017) - Thomas, Rhian S.; Alsaqati, Mouhamed; Bice, Justin S.; Hvoslef-Eide, Martha; Good, Mark A.; Kidd, Emma J.
Abstract : A major risk factor for the development of Alzheimer's disease (AD) is increasing age, but the reason behind this association has not been identified. It is thought that the changes in endocytosis seen in AD patients are causal for this condition. Thus, we hypothesized that the increased risk of developing AD associated with ageing may be because of changes in endocytosis. We investigated using Western blotting whether the expression of endocytic proteins involved in clathrin-mediated and clathrin-independent endocytosis are altered by increasing age in a mouse model of amyloid pathology. We used mice transgenic for human amyloid precursor protein containing the V717I London mutation. We compared the London mutation mice with age-matched wild-type (WT) controls at three ages, 3, 9 and 18 months, representing different stages in the development of pathology in this model. Having verified that the London mutation mice overexpressed amyloid precursor protein and β-amyloid, we found that the expression of the smallest isoform of PICALM, a key protein involved in the regulation of clathrin-coated pit formation, was significantly increased in WT mice, but decreased in the London mutation mice with age. PICALM levels in WT 18-month mice and clathrin levels in WT 9-month mice were significantly higher than those in the London mutation mice of the same ages. The expression of caveolin-1, involved in clathrin-independent endocytosis, was significantly increased with age in all mice. Our results suggest that endocytic processes could be altered by the ageing process and such changes could partly explain the association between ageing and AD. Abstract : Supplemental Digital Content is available in the text.